2014
DOI: 10.1007/s12070-014-0765-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipomas of the Oral Cavity: Clinicopathological and Immunohistochemical Study of 24 Cases and Review of the Literature

Abstract: Although lipomas are common soft tissue tumors, few cases of lipoma or its variants have been reported in the oral cavity. We here described the clinical, histological, and immunohistochemical features of 24 cases of oral lipoma obtained from medical records at Nagasaki University Hospital between 1977 and 2010, and also retrospectively reviewed 603 cases of oral lipoma reported in the English literatures. The patients examined comprised 11 men and 13 women with a mean age of 59 years, ranging from 31 to 90 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 22 publications
4
64
0
17
Order By: Relevance
“…In this context, Bajpai et al have recently discussed regarding the difficulty of differential diagnosis between some of these entities. For example, spindle cell lipoma, also called as pleomorphic adenoma, is a rare variant of lipoma histopathologically characterized by an admixture of mature fat cells with spindle cells and occasionally mast cells with myxoid connective tissue stroma which sometimes, simulates the features of neurofibroma on histopathological examination, and the final diagnosis of SCL was made on the basis of immunohistochemical features . We believe, the long period of inclusion data, and overall the different histopathological criteria of different countries and pathologist, maybe create some misdiagnosis in certain specific types of OL; however, the identification of malignancies is still the key point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Bajpai et al have recently discussed regarding the difficulty of differential diagnosis between some of these entities. For example, spindle cell lipoma, also called as pleomorphic adenoma, is a rare variant of lipoma histopathologically characterized by an admixture of mature fat cells with spindle cells and occasionally mast cells with myxoid connective tissue stroma which sometimes, simulates the features of neurofibroma on histopathological examination, and the final diagnosis of SCL was made on the basis of immunohistochemical features . We believe, the long period of inclusion data, and overall the different histopathological criteria of different countries and pathologist, maybe create some misdiagnosis in certain specific types of OL; however, the identification of malignancies is still the key point.…”
Section: Discussionmentioning
confidence: 99%
“…The latter type was not found among the basis of immunohistochemical features. 26 We believe, the long period of inclusion data, and overall the different histopathological criteria of different countries and pathologist, maybe create some misdiagnosis in certain specific types of OL; however, the identification of malignancies is still the key point.…”
Section: Clinical Differential Diagnosis Of Oral Lipoma Must Be Perfomentioning
confidence: 99%
“…Rare cases of congenital lipomas have been reported in infants of 20 and 47 days of age. A study by Naruse et al, in which the authors analyze the clinical pathologic characteristics and proliferative activities of 24 cases of oral lipomas in a Japanese population, compared with the results of various studies reporting approximately 603 cases, revealed that the average age of onset of this lesion was 59 years, and out of the 24 cases in the study, 22 corresponded to gingival lipomas, while 2 cases corresponded to fibrolipomas, 28 which histologically differ from the classic variant in which mature adipose tissue is intercalated with bands of connective tissue. This benign tumor of soft tissue rarely occurs in the oral and maxillofacial region; however, if it happens, is most frequently present in the buccal mucosa and the buccal area, also showing a slight predominance in women.…”
Section: Discussionmentioning
confidence: 96%
“…Lipoma is a submucosal lesion, sessile or pedunculated, covered by healthy mucosa, consisted of a yellow, lobulated, circumscribed and soft mass, in most cases not exceeding 1cm in diameter. Histologically, it is a mature white adipose tissue without atypia and it can be found in the variant of fibrolipoma [2]. When an oral lipoma occurs, a surgical treatment is required.…”
Section: Published: 12 December 2019mentioning
confidence: 99%